Lecturers’ perception on students’ critical thinking skills development and problems faced by students in developing their critical thinking skills - Astuti Muh. Amin; Romi Adiansyah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2018)
Critical thinking emerges when learners attempt to use their background knowledge to construct meaning through interpreting, analyzing, and manipulating information in responding to a problem or a question that requires more than a single correct answer. Two factors that affect the improvement of the students’ critical thinking skills are lecturers’ activities and students’ activities. This study was a descriptive quantitative study which aimed to investigate (1) how lecturers perceive the development of students’ critical thinking skills and (2) drawbacks or obstacles that hinder the development of students’ critical thinking skills. The type of this research is a survey research with the descriptive quantitative approach. The research samples were taken from the population by using purposive sampling technique. Data was collected using a questionnaire, an observation sheet, and interviews. The research findings are 32.05% of the lecturers evaluated their students' critical thinking skills; therefore, promoting lecturers' awareness of developing students' critical thinking skills is necessary. In addition, the results of the present study also indicated that the development of students' critical thinking skills could interfere with many aspects including lecturers, students, frequencies of scientific meetings, and facilities.